الفكر السياسي الإسلامي... بين الثابت والمتغير - فرج, عبد الحميد (جامعة الوادي University of Eloued, 2018)
عرف الفكر السياسي الإسلامي على مر العصور العديد من التجاذبات والاختلافات في الرُّؤَى والـمفاهيم ولم يستطع المفكرين العاملين في الفكر السياسي الإسلامي الإتفاق حولها ، ولم تُوضع لها قواعد محددة ودقيقة تحقق الإجماع بينهم ، وخاصة في الـمجال السياسي ، حيث أنه وبعد وفاة الرسول (عليه السلام) مباشرة ، وبداية من إنشاء نظام الخلافة الإسلامي من طرف الخلفاء الراشدين() ، ظهرت هناك عدة إشكاليات في المسائل السياسية . ثم ما لبثت أن تعمقت هذه الإشكاليات أكثر فأكثر بعد نهاية حكم الخلفاء الراشدين () وتأسيس الدولة الأموية ثم العباسية وغيرها......إلخ، وظهرت إجتهادات الصحابة والتابعين() في محاولاتهم لحل هذه الإشكاليات ، نظرا لإختلاف فهم كل واحد منهم لأسس وقواعد الدين الإسلامي ، وهو ما أدى إلى اختلاف الرؤى و الإجتهادات بداية من الإختلاف حول خليفة الرسول (عليه السلام) ، مرورا بشكل الحكم الـمعتمد ، ووصولا إلى التباين اليوم حول طبيعة وشكل نظام الحكم الذي يجب إعتماده ، ومدى توافق الأنظمة السياسية المعاصرة والياتها ومقوماتها مع قواعد وأسس ومبادئ النظام السياسي الإسلامي ، و هل حدد الإسلام شكلا معينا ومحددًا لنظام الحكم ، يسير وفقه المسلمون في كل زمان ومكان؟ أم ترك ذلك لاجتهادات البشر حسب ظروفهم الزمانية والـمكانية ؟ وهل السياسة ونظام الحكم يعتبران من أصول أم من فروع الدين الإسلامي أم لا علاقة له بهما؟ ... ، بل ومنهم من ذهب لأبعد من ذلك حين راح يدرس مسألة وجود النظام السياسي الإسلامي من عدمه أصلا. وهي الإشكالية التي سنحاول الإجابة عنها في هذه المقال : إلى أي مدى يمكن الإجتهاد في المسائل السياسية في الفكر السياسي الإسلامي ؟ أو بمعنى آخر : هل حدد وضبط الفكر السياسي الاسلامي كل المسائل السياسية وأوجب على المسلمين اتباعها في كل مكان وزمان ، ام ترك الباب مفتوحا للاجتهاد في تلك المسائل بما يتماشى مع متغيرات الزمان والمكان ، ويحقق المصلحة العامة للمسلمين؟ وسنحاول الاجابة على هذه الاشكالية من خلال ثلاث مباحث هي : المبحث الأول: مدى علاقة الإسلام (الدين) بالسياسية ...إتصال أم انفصال ؟ المبحث الثاني : هل السياسة من أصول الدين أم من فروعه ؟ المبحث الثالث : الإجتهاد في الفكر السياسي الإسلامي : بين الالتزام بالنص والاجتهاد فيه Abstract Throughout the ages, Islamic political thought known many interactions and differences in visions and concepts, the thinkers working in Islamic political thought have not been able to agree on them, they have not set specific and accurate rules to achieve consensus among them, especially in the political sphere, after the death of the Prophet (peace be upon him) directly, and the beginning of the establishment of the Islamic Caliphate system by the Caliphs, there emerged several problems in political issues. These problems became deeper and deeper after the end of the rule of the caliphs and the establishment of the Umayyad then Abbasid,…. Etc, the jurisprudence of the Companions and followers emerged in their attempts to solve these problems, due to the difference in understanding each one of them of the foundations and rules of the Islamic religion, which led to different visions and interpretations starting from the successor of the Prophet (peace be upon him), passing through the form of governance, arriving to today's variation on the nature and form of the system of government should be adopted, and the compatibility of contemporary political system and its mechanisms, and components with the foundations, rules and Principles of the political system, and has Islam determined a specific and limited form to the system of governance, which Muslims follow at every time and place? Or is it left to human judgment according to their temporal and spatial conditions? Is politics and governance considered to be of the origin or not of the branches of Islamic religion? and even some of them went further when they studied the existence of the Islamic system or not. The problem that we shall try to answer in this article is: to what extent can ijtihad on political issues in Islamic political thought? In other words, did the Islamic political thought determine and control all political issues and Obliged Muslims to follow them everywhere and at any time, or did they let ijtihad in these matters according to the variables of time and place and achieve the general interest of Muslims?
Keywords: الفكر؛ السياسي ؛ الإسلامي